Pembagian Harta Waris Kepada Ahli Waris Dari Perkawinan Pertama Dan Kedua Ditinjau Dari Kitab Undang-Undang Hukum Perdata - Weldo Parinussa; Merry Tjoanda; Barzah Latupono (Faculty of Law, Universitas Pattimura, 2021)
Introduction: The distribution of inheritance to the heirs of the first and second marriages in terms of the civil law code. Regarding the inheritance controlled by the children of the second wife without sharing with the children of the first wife after the death of the father.Purposes of the Research: The purpose of this study is that inheritance can be divided fairly according to civil law.Methods of the Research: The research method used is juridical normative, the problem approach used in the research is the statutory approach and the conceptual approach. Sources of legal materials used are primary, secondary and tertiary legal materials. The technique of collecting legal materials used in this study is a research library, then analyzed using qualitative methods.Results of the Research: The results of the study show that if the husband who dies leaving children from both the first wife and the second wife is an heir, then when the inheritance is open to be divided, according to article 35 paragraph (1) of the marriage law, it is stated that property obtained by marriage becomes property. together, then the property must be divided into 2 parts first, where the part becomes the right of the husband and becomes part of the wife in accordance with the provisions on the distribution of joint assets based on Article 128 of the Civil Code. Then the children will get a share from the father's side and the mother's side because civil law adheres to the bilateral principle in the distribution of inheritance and the inheritance share of boys and girls is not distinguished so that they each get the same amount. And after the father remarries, there will be a distribution of assets after the father dies to the children from the first and second marriages. Based on the provisions of Article 852 of the Civil Code: Children or descendants, even though born and various marriages, the inheritance of their parents, their grandparents, or their subsequent blood relatives in a straight line upward, regardless of gender or birth first.